Effects of preparation temperature on production of graphene oxide by novel chemical processing. Issue 7 (1st April 2021) - Al-Gaashani, Rashad; Zakaria, Yahya; Lee, One-Sun; Ponraj, Janarthanan; Kochkodan, Viktor; Atieh, Muataz A.
Abstract: The effect of preparation temperature on the synthesis of high quality graphene oxide (GO) by a chemical oxidation method has been studied. GO samples have been produced from graphite using a blend of sulfuric and phosphoric acids with a volume ratio of 4:1, where potassium permanganate and hydrogen peroxide were selected as oxidizing agents. The temperature for GO preparation was changed over a range of 20–85 °C. The synthesized GO samples have been characterized by X-ray diffraction, scanning electron microscopy, electron dispersive spectroscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy (XPS), and ultraviolet–visible spectroscopy methods. It was shown that high quality GO can be synthesized at 20 °C but the purity of GO increased with the increase of the preparation temperature. The atomistic models of GO sheets prepared at different temperatures and according to the stoichiometric ratio of the functional groups found by XPS have been developed. Based on the developed models it was found that GO prepared at higher temperatures had more holes in the sheets supported with experimental images.